(untitled) (Research, Society and Development, 2021)
The objective of the study was to analyze reasons of interest and lack of interest of dental students in the public labor market, under the bias of policies that induce (re) orientation of academic health education. Qualitative research, through recorded individual interview and guide script, with a sample defined by the saturation method, in a public university in Paraná was carried out in 2017. The thematic content analysis identified five categories: stability and professional career; experiences lived during training; work process in Brazilian Unified Health System (SUS); SUS user profile; social return. The experiences lived during the academic formation suggest to direct the profile of the desired job market. Still, the experience in the SUS work process seems to be able to develop a more critical and realistic view of the profession and the public sector, directing it to more assertive professional choices.